Volumetric Bone Mineral Density Assessed by Dual-Energy CT Predicts Bone Strength Suitability for Cementless Total Knee Arthroplasty - Dong Hwan Lee; Dai-Soon Kwak; Sheen-Woo Lee; Yong Deok Kim; Nicole Cho; In Jun Koh (Medicina)
Background and Objectives: Adequate bone quality is essential for promoting initial bone ingrowth and preventing early migration during cementless total knee arthroplasty (TKA). However, gold-standard criteria for identifying suitable bone strength have yet to be established. Dual-energy computed tomography (DECT)-based volumetric bone mineral density (vBMD) is an emerging tool for assessing bone quality. This study aimed to determine whether DECT-derived vBMD can accurately predict suitable bone strength for cementless TKA. Materials and Methods: A total of 190 patients undergoing primary TKA with a standardized posterior-stabilized implant were prospectively enrolled. Prior to TKA, DECT-derived vBMD was measured in the femoral box region. Actual bone strength was evaluated using an indentation test on resected femoral box specimens. Correlation and linear regression analyses were performed to assess the relationship between DECT vBMD and actual bone strength. Receiver operating characteristic (ROC) curve analysis and area under the curve (AUC) calculations were used to determine the optimal cut-off value and diagnostic accuracy of DECT vBMD in identifying candidates suitable for cementless TKA. Results: DECT-derived vBMD exhibited a strong correlation with actual bone strength (correlation coefficient = 0.719, p < 0.01), while linear regression analysis revealed a moderate association (R2 = 0.51, p < 0.01). In addition, it demonstrated excellent diagnostic performance in predicting adequate bone quality for cementless TKA, yielding an AUC of 0.984, with a sensitivity of 91.9% and a specificity of 92.0%. Conclusions: DECT-derived vBMD is a reliable and accurate tool for assessing bone strength around the knee and predicting the suitable bone quality for cementless TKA.